MATERNAL MORTALITY IN A TERTIARY CARE HOSPITAL - Fawad, Anisa; Naz, Humaira; Islam, Ansa; Zaffar, Seemab; Abbasi, Aziz -un-Nisa (Journal of Ayub Medical College Abbottabad, 2011)
Background: Death of a woman during pregnancy and child birth is an extremely tragic event. It is a waste of a precious life that leaves great feeling of grief and pain for the family and hospital staff and has devastating influence on the community overall. Maternal morbidity and mortality can be prevented by awareness of reproductive health in a community, availability, and utilisation of organised antenatal care, skilled intrapartum management and careful postnatal follow up. Objective was to analyse the pattern of maternal mortality over the period of five years in a tertiary level hospital receiving high risk referred patients form periphery. Methods: All patients admitted in Gynae ’˜A’ Unit, Ayub Teaching Hospital from January 2006 to December 2010 were included in the study and number and causes of maternal deaths were noted. Results: During these 5 years there were 78 maternal deaths out of 11,997 obstetrical admissions. There were 7,380 total births and 78 maternal deaths during the study period and Maternal Mortality Rate was 1,057/100,000. The main cause of maternal death was eclampsia and its complications (28.2%). Conclusion: Eclampsia is the leading cause of maternal mortality in our setup. Proper and timely referral is an important measure to prevent it. Keywords: Maternal mortality, Eclampsia, Septicaemia, Haemorrhage, Pulmonary embolism, Antenatal care